2013
DOI: 10.1161/circulationaha.112.130179
|View full text |Cite
|
Sign up to set email alerts
|

Hemopexin Therapy Improves Cardiovascular Function by Preventing Heme-Induced Endothelial Toxicity in Mouse Models of Hemolytic Diseases

Abstract: Background-Hemolytic diseases are characterized by enhanced intravascular hemolysis resulting in heme-catalyzed reactive oxygen species generation, which leads to endothelial dysfunction and oxidative damage. Hemopexin (Hx) is a plasma heme scavenger able to prevent endothelial damage and tissue congestion in a model of heme overload. Here, we tested whether Hx could be used as a therapeutic tool to counteract heme toxic effects on the cardiovascular system in hemolytic diseases. Methods and Results-By using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
240
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 203 publications
(256 citation statements)
references
References 52 publications
13
240
0
3
Order By: Relevance
“…Recently, we showed that, by scavenging heme, Hx prevents heme accumulation in endothelial and immune cells, thus limiting heme toxicity [9,36]. To evaluate whether cardiomyocytes (CMs) may also be affected by pathologic free heme, we treated mouse neonatal CMs with 10 µM heme, in presence of either Hx or Albumin (a low affinity heme-binding protein [17]).…”
Section: Hemopexin Protects Neonatal Cardiomyocytes From Heme Accumulmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we showed that, by scavenging heme, Hx prevents heme accumulation in endothelial and immune cells, thus limiting heme toxicity [9,36]. To evaluate whether cardiomyocytes (CMs) may also be affected by pathologic free heme, we treated mouse neonatal CMs with 10 µM heme, in presence of either Hx or Albumin (a low affinity heme-binding protein [17]).…”
Section: Hemopexin Protects Neonatal Cardiomyocytes From Heme Accumulmentioning
confidence: 99%
“…Heme promotes endothelial dysfunction by inducing the expression of adhesion molecules and reducing nitric oxide (NO) availability, which causes vasoconstriction [9][10][11][12][13][14]. Moreover, heme-derived ROS induce the proliferation of smooth muscle cells, that participate in vasculopathy associated with atherosclerosis and hypertension [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Gelderman, Baek and co-authors showed that hemopexin as well as haptoglobin supplementation does not alter plasma iron levels or tissue iron loading. 8 This indicates that in the Hbb th3/+ mouse model the rate of intravascular hemolysis does not contribute significantly to hemochromatosis.…”
Section: Th1/th1mentioning
confidence: 99%